(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Vermicomposting is a process in which earth worms are used to convert organic materials into humus - like material known as vermicompost. Nutrient profile in the vermicompost is generally higher than tradition compost. In fact, vermicompost can enhance soil fertility, physically, chemically and biologically. Physically, vermicompost treated soil has better aeration, porosity, bulk density and water retention. The chemical properties such as pH, electrical conductivity and organic matter content are also improved for better crop yield. Nevertheless, the enhanced plant growth could not be satisfactorily explained by improvements in the nutrient content of the soil, which means that other plant growth influencing materials are available in the vermicomposts. Although vermicompost have been shown to improve plant growth significantly, the application of vermicomposts could impede the growth due to the high concentrations of soluble salts available in the vremicomposts. Therefore, vermicomposts should be applied at moderate concentration in order to obtain maximum plant yield. This review paper discussed in detail the effects of vermicompost in soil fertility physically, chemically and biologically. Future prospects and economy on the use of organic fertilizers in agriculture sector were also examined.